Hydroxamic acids : a unique family of chemicals with multiple biological activities - Gupta, Satya P. (Springer Berlin Heidelberg, 2013)
Satya P. Gupta's Hydroxamics Acids is the first book to compile invited articles written by international experts on the class of compounds hydroxamic acids. Found to possess a wide spectrum of biological activities, the hydroxamic acids are of interest for  theoretical and experimental chemists who can study and make use of them in drug design and development. Chapters in this book provide a diverse and comprehensive coverage of this compound class and consequently this publication is a valuable resource for researchers in chemical, pharmaceutical and biological sciences.